How public and government matter in industrial pollution mitigation performance: Evidence from China. (15th July 2021) - Dong, Feng; Pan, Yuling; Li, Yangfan; Zhang, Shuaiqing
Abstract: Every country must face the problem of controlling industrial pollution during industrialization. Although low-carbon development has become important to global economic development, industrial pollution remains a problem in rapidly industrializing developing countries. With China as a case study, this paper utilizes the Malmquist index based on game cross-efficiency to measure the industrial pollution mitigation performance (IPMP) in each province of China. Labor and money variables related to industrial pollution mitigation are taken as the input indexes, and the reduction rate of various industrial pollution emissions are taken as the output indexes. From the perspectives of the public and the government, this paper further explores the influencing factors on the IPMP. Considering that there may be a nonlinear relationship between the influencing factors and the IPMP, nonparametric kernel regression is employed to explore the effect by the influencing factors, and the nonparametric bivariate density estimation is used to verify the regression results. The main conclusions of this study are as follows: (1) Due to the concentration of heavy industry, the IPMP is low in northern China. In contrast, the IPMP in central and western China is relatively high. (2) Public supervision has a positive impact on the IPMP. However, the results of heterogeneity analysis show that this effect is different in eastern, central and western China. As a result, under a high degree of public supervision, the regional IPMP will be significantly improved. (3) Public concentration has a positive "U"-shaped impact on the IPMP. The heterogeneity analysis shows that eastern China also has this "U"-shaped characteristic, while the public concentration of central and western China has a positive impact on the IPMP; that is, similar to the public supervision, under a high degree of public concentration, the regional IPMP will be significantly improved. (4) In areas where the enforcement of environmental law is strict, government supervision has a positive impact on the IPMP. By contrast, in areas where environmental law enforcement is not strict, government supervision does not have a positive impact on the IPMP. (5) Due to the failures of policy design and implementation, government concentration has a negative impact on the IPMP. China is the largest developing country in the world. It is of great significance to study its IPMP and the roles of public and government, as it provides other developing countries with insights regarding the experience of industrial pollution control. Highlights: The IPMP in northern China is relatively low. The IPMP in central and western China is relatively high. Public power can make positive impact on the IPMP with large scale. Government supervision and concentration fail to improve the IPMP.